Answer:
i = 323 A
Step-by-step explanation:
Initial flux due to magnetic field from the coil is given as
![\phi = NB.A](https://img.qammunity.org/2020/formulas/physics/college/ctyt68xqw6hwb5rka68wbvtjf5v064ze8w.png)
here we will have
![N = 190](https://img.qammunity.org/2020/formulas/physics/college/a0vnelpbly7vix78kwrjpz6rv1f1z7c0u4.png)
![B = 1.60 T](https://img.qammunity.org/2020/formulas/physics/college/imf633jv1acka751xadgbikf1t85jkn9nu.png)
![A = 0.340 m^2](https://img.qammunity.org/2020/formulas/physics/college/emls89czlvvfp37b46dxcsyfmck3649fjo.png)
now the flux is given as
![\phi_1 = (190)(1.60)(0.340) = 103.36 T m^2](https://img.qammunity.org/2020/formulas/physics/college/6bi34y8zj57jshwkvhbxbeqmic2ree70o8.png)
finally current in the electromagnet changed to zero
so final flux in the coil is zero
![\phi_2 = 0](https://img.qammunity.org/2020/formulas/physics/college/9jvpqx0qok0lwofddurrlqt9eviwqruuyx.png)
now we know that rate of change in flux will induce EMF in the coil
so we will have
![EMF = (\phi_1 - \phi_2)/(\Delta t)](https://img.qammunity.org/2020/formulas/physics/college/1b9mkyowbj0skj0ls3t0huns43nyga4olc.png)
![EMF = (103.36 - 0)/(20 * 10^(-3))](https://img.qammunity.org/2020/formulas/physics/college/fvcszys8anqslhidppvjgixzi28gvccvkf.png)
![EMF = 5168 Volts](https://img.qammunity.org/2020/formulas/physics/college/xipruhbddkqvs0zitxwmyvyjqycmohis9l.png)
now induced current is given as
![i = (EMF)/(R)](https://img.qammunity.org/2020/formulas/physics/college/d1s0rfu6xb6v4woxcdbtpen7ffr0oihvp2.png)
![i = (5168)/(16) = 323 A](https://img.qammunity.org/2020/formulas/physics/college/3i6pil9htsy37qipd4iyicupgv2yfcvth5.png)